Always too long: My short-film experience. Issue 1 (1st January 2015) - Bal, Mieke
Attempting to explain, in a short film, a theoretical concept that underlies our the feature film Madame B (Bal & Williams Gamaker, 2014), I discovered that narrativity and description, always in tension, merge into more clarity as the film gets shorter.